SHAPE AND SIZE IN MEDICINE, BIOTECHNOLOGY, MATERIALS SCIENCE AND SOCIAL SCIENCES - Bongiorno, Enea G; Micheletti, Alessandra; Naldi, Giovanni; La Torre, Davide (Image Analysis and Stereology, 2011)
This special issue gathers together papers presented during the workshop Shape and Size in Medicine, Biotechnology, Materials Science and Social Sciences, Milano, Italy, 16-17 February 2011, https://sites.google.com/site/shapemilan/home